Peran Pembimbing Kemasyarakatan dalam Meningkatkan Self-Control Klien Pemasyarakatan di Bapas Kelas I Yogyakarta - Rigar Satria Elha Ramadhan; Ali Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Self-control is an individual's ability to direct, manage, regulate, and direct themselves in a positive direction. In general, people with high self-control are able to refrain from actions that go against the norms and regulations enforced in society. Inmates who have just been released from a correctional facility become correctional clients of the correctional facility. Correctional Centers are tasked with providing supervision and guidance through community counselors. One of those counseling is for helping prison inmates gain acceptance into society and strengthen their self-control to avoid criminal cases again.